If it's not what You are looking for type in the equation solver your own equation and let us solve it.
(3x+4)+(x+1)=4(x-1)+10
We simplify the equation to the form, which is simple to understand
(3x+4)+(x+1)=4(x-1)+10
Remove unnecessary parentheses
3x+4+(x+1)=4*(x-1)+10
Remove unnecessary parentheses
+3x+4+x+1=+4+*(+x-1+)+10
Reorder the terms in parentheses
3x+4x+1=+(+4x-4)+10
Remove unnecessary parentheses
+3x+4+x+1=+4x-4+10
We move all terms containing x to the left and all other terms to the right.
+3x+1x-4x=-4+10-4-1
We simplify left and right side of the equation.
0x=+1
0=1
The left and right sides are not equal, therefore there is no solution. This equation is invalid.
| 6d-15=33 | | m/4=6/5 | | -(4x-7y+1)= | | 5t-t-3=3t-5 | | 2(4-2x)=4 | | -5(5x+9)=55 | | 68/4*3= | | 4y+4y=7y-3 | | 129-2x=16x+23 | | x+7=39-x | | 8x=4(8x+24) | | -6x+6=-3x-9 | | 8x=32x+96 | | 6d+8.7=d+d | | 1.3x+5-1.48x=-.6x-.84+5 | | -6x+6=-3x-8 | | 80x^2+8x=24 | | -6x+3=6x+27 | | 1+5x=-7x+85 | | 4+v=9 | | 9+9x-5=22 | | -5(r+4)= | | 7n+5m+8m+3n= | | x^2-3x-13=6x-21 | | -7x+4-3x=-66 | | 18.8=4w+2.4 | | 8+4x+2x=68 | | 3x+5=7x+18 | | L-7=-4 | | 7-5x+3x=9 | | 1=a | | -402=6(7x-11) |